2015
DOI: 10.1007/s10735-015-9624-5
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated expression of ILF2 in non-small cell lung cancer is associated with tumor cell proliferation and poor prognosis

Abstract: ILF2 (NF45) is a sequence-specific DNA binding protein that is involved in mitosis control, transcriptional regulation, DNA breaks repair, microRNA processing and viral replication. In the present study, we aim to investigate the potential role of ILF2 in the progression of non-small cell lung cancer (NSCLC). Western blot analysis indicated that ILF2 was up-regulated in NSCLC tissues, compared with adjacent non-tumorous ones. Furthermore, immunohistochemistry analysis showed that the expression of ILF2 was cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 37 publications
1
27
1
Order By: Relevance
“…Previous studies have demonstrated that environmental deterioration, tobacco use, radon exposure and occupational carcinogens are risk factors for lung cancer (4)(5)(6)(7). Lung cancer is divided into two major clinically relevant groups, small cell lung cancer and non-small cell lung cancer (NSCLC), according to histological analysis (8). NSCLC is the predominant type of lung cancer and accounts for ~83% of all cases (9).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that environmental deterioration, tobacco use, radon exposure and occupational carcinogens are risk factors for lung cancer (4)(5)(6)(7). Lung cancer is divided into two major clinically relevant groups, small cell lung cancer and non-small cell lung cancer (NSCLC), according to histological analysis (8). NSCLC is the predominant type of lung cancer and accounts for ~83% of all cases (9).…”
Section: Introductionmentioning
confidence: 99%
“…In this gene set, upregulation of 27 genes was associated with poor PFS. These genes include genes that have known functions in the regulation of the ER transcriptional network (TFAP2C 18, 19 and SP1 20, 21 ), genes that have been shown to be related to breast cancer biology and clinical outcomes (TFAP2C, BMPR1A 22 , ARRDC3 23 , PPP2R3A 24 ) and genes not yet reported to be related to breast cancer but with functional roles in tumorigenesis, metastases and response to treatment in other cancer types and may also have molecular functions in breast cancer (ILF2 25 , ATP11B 26 , CSDA 27 , USP5 28 ,TANC1 29 , NOTCH2 30 , ADD3 31 and SEC23A 32 ). In addition, there are a number of genes in the gene set that do not have known roles in cancer biology (CCDC93, CPNE1, GLTP and TCEB3).…”
Section: Resultsmentioning
confidence: 99%
“…The kinetics of NF90 and NF45 chromatin association at these proximal promoters is consistent with NF90 and NF45 serving essential roles in regulating the rapid induction of IEGs that occurs on the timescale of 30 minutes to 2 hours. (26,27) and diverse cancers (28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…disruption of NF90 and NF45 impaired ESC proliferation and promoted differentiation to an epiblast-like state (27). NF90 and NF45 regulate cell cycle progression (18,19,28), cell growth and proliferation (28)(29)(30)(31)(32)(33), and are amplified, overexpressed and mutated in diverse cancers (34,35).…”
Section: Introductionmentioning
confidence: 99%